Collaborative leadership six influences that matter most - DeWitt, Peter M. (Corwin, a SAGE Company, 2017)
Get the ammunition you need to fuel collaborative leadership in your school. What type of leadership do you practice? Many of us rely on transformational and instructional leadership. But there are advantages in applying a holistic angle including all stakeholders--an approach known as collaborative leadership. Peter DeWitt unpacks six factors framed through John Hattie's research while painting a powerful scheme: meet stakeholders where they are, motivate stakeholders to strive for improvement, model how to do it.